What effect does increasing the retirement age have on the employment rate older women? Empirical evidence from retirement age hikes in Hungary during the 2000s - Zsombor Cseres-Gergely (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
This paper provides empirical evidence on the effect of changing the retirement age on employment. Base on individual data from Hungary, a country where a number of hikes increased the retirement age between 1997 and 2009, this analysis benefits from substantial variation in pension eligibility during a relatively short time. It is based on a difference-in-difference approach and supported by independent variation in the age-based eligibility rule contributing to the causal identification of the effect. Results suggest that the effect of the changes in early retirement age is substantial, amounting to 5-7.4 percentage point increase in the 45 per cent employment rate at the retirement age for women. Changes in the normal retirement age do not seem to have such employment effect because increases in disability pension claims have counteracted them.
Keywords: H31; H55; J14; J26; 330; retirement age; older workers; employment